Advances in 3D cell culture for liver preclinical studies. (11th May 2021) - Yao, Ting; Zhang, Yi; Lv, Mengjiao; Zang, Guoqing; Ng, Soon Seng; Chen, Xiaohua
Abstract: The 3D cell culture model is an indispensable tool in the study of liver biology in the field of health and disease and the development of clinically relevant products for liver therapies. The 3D culture model captures critical factors of the microenvironmental niche required by hepatocytes for exhibiting optimal phenotypes, thus enabling the pursuit of a range of preclinical studies that are not entirely feasible in conventional 2D cell models. In this review, we highlight the major attributes associated with and the components needed for the development of a functional 3D liver culture model for a range of applications.